Flexible markets, stable societies? - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2008)
The dissolution of the standard employment relationship since the 1970s has been paralleled by a destabilization of family relations. The paper, which is a slightly revised version of a plenary lecture at the 2008 Meeting of the German Sociological Association, discusses possible connections between the rise of more flexible labor market and family structures, and explores how they might tie in with the declining birth rate. The co-evolution of labor markets and family relations can be explained by both the attractions and the constraints of free markets. The current shift toward a new social policy aimed at increasing fertility is presented as an example of how expanding market relations and the uncertainty to which they give rise in personal life cause demands for state intervention. The logic seems remarkably similar to that of the current banking crisis, where the liberation of financial markets from traditional constraints and the progressive commodification of money have ultimately issued in irresistible pressures on the state to step in and restore the social commons of stable expectations and mutual confidence. In both cases, and perhaps generally, capitalism seems to imply a need for a public power capable of creating substitutes for social relations invaded by market relations and as a consequence losing their capacity to perform some of their previous functions. – – Parallel zum Niedergang des Normalarbeitsverhältnisses seit den Siebzigerjahren haben auch die familiären Beziehungen an institutioneller Verbindlichkeit verloren. Das Papier - die leicht überarbeitete Fassung eines Plenarvortrags beim 34. Deutschen Soziologentag im Oktober 2008 - diskutiert mögliche Zusammenhänge zwischen der Flexibilisierung von Arbeitsmärkten und Familienstrukturen und setzt diese in Beziehung zu der gleichzeitig gesunkenen Geburtenrate. Als Ursache der Koevolution von Arbeitsmärkten und Familienbeziehungen kommen sowohl die Attraktivität freier Märkte als auch die von ihnen ausgehenden wirtschaftlichen Zwänge in Frage. Der gegenwärtige Übergang zu einer neuen, auf Hebung der Geburtenrate zielenden Sozialpolitik ist ein Beispiel, wie die Expansion von Marktbeziehungen und die von ihr ausgehende Unsicherheit auch der persönlichen Lebensverhältnisse Forderungen nach staatlicher Intervention nach sich zieht. Die Logik ist dieselbe wie in der Bankenkrise, wo die Befreiung der Kapitalmärkte von traditionellen Beschränkungen und die zunehmende Kommodifizierung des Geldes den Staat gezwungen haben, mit öffentlichen Mitteln stabile Erwartungen und gegenseitiges Vertrauen wiederherzustellen. In beiden Fällen, und wahrscheinlich generell, erzeugt Kapitalismus ein Bedürfnis nach staatlicher Ersatzbeschaffung für soziale Beziehungen, die als Folge ihrer Vermarktung ihre ursprünglichen Funktionen nicht mehr zu erfüllen vermögen.
Keywords: 300